Exploring Language Learning through Culture: Indigenisation of English in a Pakistani Context - Hafiz Nauman Ahmed; Muhammad Islam; Ali Rizwan Pasha (Linguistics and Literature Review, 2023)
The study aims to explore the cultural facets of learning and using English language in a Pakistani context. Drawing on information collected from participants, the study also indicates the present status of the indigenisation of English in Pakistan. This mixed-method research used a convenience sampling strategy to collect data from 476 students through a questionnaire and from 15 teachers through semi-structured interviews. The findings of the study revealed that there is little explicit focus on culture during the teaching and learning of the English language. The collected data also show that students learn the target culture more than the local culture, mainly due to the use of foreign teaching materials. Moreover, both students and teachers seem ambivalent about the Indigenisation of English in Pakistan, although a shift in the status of English can be observed in its teaching and learning processes. The study further suggested to develop materials based on the local context in order to incorporate local culture and make English more indigenous.